FASILITASI AKSES PEMBIAYAAN BAGI PELAKU UMKM TERDAMPAK COVID-19 DI BANDA ACEH - Hamdani Hamdani; Josi Farmiati; Munawir Munawir (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2021)
Community service focuses on MSMEs affected by Covid-19 for businesses run by 32 business actors in Banda Aceh City. The form of activity is in the form of specific business assistance in financing facilitation to bank financial institutions to obtain working capital and investment. The facilitation method carried out is in the form of training on credit and banking, business mentoring, and business coaching which lasts for 3 months involving cross-related agencies. The results of the service activities are the increasing number of MSMEs that are bankable and fulfill aspects of good business management in accordance with bank requirements to obtain business capital loans. Of the 32 program participants, 62.5 percent are already bankable, while 37.5 percent need further assistance.